2004
DOI: 10.1111/j.1468-0297.2004.00245.x
|View full text |Cite
|
Sign up to set email alerts
|

Solow and Heterogeneous Labour: A Neoclassical Explanation of Wage Inequality

Abstract: This paper analyses the effect of human-capital investments of heterogeneous individuals on the dynamics of the wage structure within a neoclassical growth model. The accumulation of physical capital changes relative factor prices and thus incentives to acquire skills, thereby altering the composition of the labour force. Without relying on exogenous shocks, our framework generates dynamics that resemble important observations on wage inequality (e.g., the non-monotone evolution of the skill premium). Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Incorporating Meckl and Zink's [12] idea of educational choice into Caselli's framework, this paper has analyzed the within-group inequality in addition to the between-group inequality. As a result, it is shown that, when a shock diminishes the threshold ability, such as a decrease in the skill acquisition cost, then the within-group inequality among the skilled increases but the inequality among the unskilled workers decreases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Incorporating Meckl and Zink's [12] idea of educational choice into Caselli's framework, this paper has analyzed the within-group inequality in addition to the between-group inequality. As a result, it is shown that, when a shock diminishes the threshold ability, such as a decrease in the skill acquisition cost, then the within-group inequality among the skilled increases but the inequality among the unskilled workers decreases.…”
Section: Resultsmentioning
confidence: 99%
“…Aghion [3] and Meckl and Zink [12] are important exceptions. Aghion explains the aforementioned two puzzles using a single framework in which vintages of human capital play a key role.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…This economy accommodates labor of two types: skilled laborand unskilled labor. Education costs must be incurred in order to become a skilled laborer, as assumed by Caselli (1999), Meckl and Zink (2004), Miyake, Muro, Nakamura, and Yasuoka (2009), and by Chen(2010). That cost is assumed as  .…”
Section: Householdsmentioning
confidence: 99%